2015
DOI: 10.1111/his.12660
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein gene expression is altered in oral cancer and may predict metastasis and patient outcomes

Abstract: Metallothionein mRNA expression is altered significantly in oral squamous cell carcinomas. The expression of MT1G, MT1X and MT3 may aid in the prognostic discrimination of OSCC cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…For example, zinc ions induced strong transcription of MT-1G , but not MT-1A genes, whereas nickel ions caused MT-1G expression exclusively. Inducer-specific expression of MT-1 genes has been noted in other cell types [34,44,45,46,47], supporting the hypothesis that individual isoforms have very selective metal ion sequestering functions [5,6,22,39,40,84]. Western blotting revealed that cadmium was the most potent inducer of MT-1A protein expression, whereas MT-1M protein expression was highly specific to cadmium, revealing the potential of both as biomarkers of cadmium exposure.…”
Section: Discussionmentioning
confidence: 69%
“…For example, zinc ions induced strong transcription of MT-1G , but not MT-1A genes, whereas nickel ions caused MT-1G expression exclusively. Inducer-specific expression of MT-1 genes has been noted in other cell types [34,44,45,46,47], supporting the hypothesis that individual isoforms have very selective metal ion sequestering functions [5,6,22,39,40,84]. Western blotting revealed that cadmium was the most potent inducer of MT-1A protein expression, whereas MT-1M protein expression was highly specific to cadmium, revealing the potential of both as biomarkers of cadmium exposure.…”
Section: Discussionmentioning
confidence: 69%
“…There are few reports of the association of these genes with prognosis in HCC or in other cancers. Previous studies indicate that downregulation of CXCL14 is associated with prognosis in gastric cancer patients [32], MT1X may aid in the prognostic discrimination of oral squamous cell carcinoma cases [33], and MARCO expression is associated with breast cancer survival and risk of recurrence [34]. …”
Section: Discussionmentioning
confidence: 99%
“…MTs overexpression was frequently reported to be associated with poor prognosis in a wide range of human cancers, such as hepatocellular carcinoma, breast cancer, glioblastoma, oral cancer, and melanoma [23, 3538]. Although the prognostic role of MTs in gastric cancer was also evaluated in several studies, it is still hard to conclude what exact value they possessed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the antibodies used in many studies could not specify MT1 and MT2 isoform due to their physical-chemical homology [39]. This speculation seems to be verified by the phenomenon mentioned above that the change in MT1/2 protein expression was different from single MT isoforms and different MT isoform plays distinct function in cell activities [38, 39]. Although the antibodies specific to MT1A, MT1G, and MT3 were available in market [9, 40], distinguishing of MTs by using antibodies is even more tricky.…”
Section: Discussionmentioning
confidence: 99%